2022
DOI: 10.1007/s40279-022-01764-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Concurrent Strength and Endurance Training on Measures of Physical Fitness in Healthy Middle-Aged and Older Adults: A Systematic Review with Meta-Analysis

Abstract: Background There is evidence that in older adults the combination of strength training (ST) and endurance training (ET) (i.e., concurrent training [CT]) has similar effects on measures of muscle strength and cardiorespiratory endurance (CRE) compared with single-mode ST or ET, respectively. Therefore, CT seems to be an effective method to target broad aspects of physical fitness in older adults. Objectives The aim was to examine the effects of CT on measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 119 publications
(176 reference statements)
0
16
0
Order By: Relevance
“…In contrast, CT limits explosive strength gains compared to resistance-only training, offset in the current study by performing RT before ET ( 63 ). In agreement with ( 64 ), moderate to high ET intensity was prescribed to benefit cardiorespiratory fitness and muscle strength ( 64 ). As a recent systematic review mentioned, protein intake (whey, casein, soy, milk) after an acute CT bout increases myofibrillar protein synthesis to a similar extent as after RT ( 65 ).…”
Section: Discussionmentioning
confidence: 93%
“…In contrast, CT limits explosive strength gains compared to resistance-only training, offset in the current study by performing RT before ET ( 63 ). In agreement with ( 64 ), moderate to high ET intensity was prescribed to benefit cardiorespiratory fitness and muscle strength ( 64 ). As a recent systematic review mentioned, protein intake (whey, casein, soy, milk) after an acute CT bout increases myofibrillar protein synthesis to a similar extent as after RT ( 65 ).…”
Section: Discussionmentioning
confidence: 93%
“…Individual differences in lifestyle choices and inactivity mediate the deterioration of physiological function that comes with advancing age [36]. Based from previously conducted scientific studies, at first, performance seems to hold steady until around age 35-40, then it gradually diminishes until age 50, and finally, the biggest drops in performance happen around age 70 [37,38]. This is because there is mounting data that demonstrates a decline in musculature and function (specifically, muscle strength and power) with age [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…However, our results showed that short-term tongue strengthening training in NPCR patients could increase TAR and TCR pressure, but there was no signi cant change in endurance time. The possible reasons for this discrepancy were as follows: i.Our prescription for tongue-strengthening exercises was for short periods of repetitive exercises, while the prescription for endurance training required long periods of repetitive exercises 42 ; ii.Increased tongue endurance time in patients with NPCR dysphagia is a long-term compensatory function 34 . The short-term high-intensity strengthening of tongue motor function training did not improve tongue endurance, and we will continue to observe the effect of long-term continuous high-intensity training on tongue endurance in the future.…”
Section: Segmental Tongue Function Training Can Not Improve the Tongu...mentioning
confidence: 99%